Molecular Dynamics Study of Extraordinary Elastic Deformation Found in Gold Atomic Cluster - YONEKAWA, Yoshiaki; SAITOH, Ken-ichi (Journal of Advanced Mechanical Design, Systems, and Manufacturing, 2010)
Inelastic deformation of gold (Au) atomic cluster is investigated by using molecular dynamics (MD) simulations. We performed compression and unloading tests in which silicon (Si) plates approach each other and push single Au cluster of 4 nm diameter in between. Possibility of super-elastic (hyper-elastic) behavior is first discussed in the present study. The potential function of embedded atom method is adopted inside Au cluster, whereas other interactions are formulated by simplified Lennard-Jones interaction. The cluster in MD simulation shows large recovery strain which is reversible in unloading process after compression. The recovery strain is estimated on average from 5 to 10%. It is found that there are deformation mechanisms depending on temperature of the cluster. Mechanism for low temperature is based on slip motion and that for high temperature is dominated by surface reconstruction. The strength of interaction energy between Si plate and the Au cluster which may cause pulling force and produce tensile state is investigated, referring to our AFM experiment.